Flipping the Value Creation Model. (November 2016) - Schultz, Don
Abstract: Technological innovation has enabled the reversing of the traditional marketer seeking customers through various forms of media and promotion to one where consumers are making their needs known to all via social media and other interactive forms. Thus, customers are now creating potential marketplace value which is there for the taking. This development, however, challenges marketers since they must now shift to being a marketer that can 'read and respond' to those demands. Marketers must now monitor consumer-developed interests/demands customers are creating. A new promotional planning model SIVA (Solutions, Information, Value and Access) has been introduced and explained to take advantage of that change.